Análise termohigrométrica nos eixos viários centrais da malha urbana original de Sinop - MT - Zavitoski, Érico Vinicius da Silva (2018)
Considering that the intense urbanization is directly related to changes in the urban microclimate, and that there is still a gap in the study of these influences, especially in cities located in equatorial regions. In this work a thermo hygrometric analysis was performed on the road axes of the central regions of the city of Sinop in the State of Mato Grosso, so that the results obtained from this research provided important information for the development of projects related to urban planning, as well as improvements in quality population, related to the local microclimate. The interaction of the climate with the configuration and the use of urban space can significantly affect the conditions of environmental comfort, determining the urban microclimate. In this research data were collected from climatic variables such as air temperature and relative air humidity, through the mobile transect, covering the periods hot humid, hot dry and the transition period in 2017. In the mobile transect were traversed two central routes of the Consolidated Urban Zone - ZUC, in which they intersect in two perpendicular axes between each other, covering commercial and residential regions with different structural characteristics. The mobile transect was traversed with a car where on its outer side was coupled a handmade shelter, made of PVC pipe containing in its interior a temperature sensor of the air and relative humidity of the air. This circuit was traversed within 1 hour, and climate data were collected at 17 points. The survey also counts for data validation, a fixed commercial micrometeorological station (Davis Vantage Pro2), installed in the commercial sector region of the city of Sinop. The results of this research showed evidence of the influence of the urban configuration on the climatic quality of the subdivision, where it was observed changes in the thermal and dynamic characteristics for the two analyzed situations. For the case studied, it was found that the most vegetated areas showed a decrease in air temperature, as well as in spaces where the constructive density was lower, there were records of milder temperatures. It is possible to observe that the values follow the seasonality of the region, where the rainy season is defined by high relative humidity, constant rainfall, while the dry season is well defined by abrupt drop in relative humidity, which generates discomfort for the population. This work can thus provide society and subsequent research studies, scientifically proven data of an era that may help in the characterization of the urban microclimate of the city of Sinop-MT.